Proceedings of the 2007 ACM/IEEE Conference on Supercomputing 2007
DOI: 10.1145/1362622.1362660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of active storage strategies for the lustre parallel file system

Abstract: Active Storage provides an opportunity for reducing the amount of data movement between storage and compute nodes of a parallel filesystem such as Lustre, and PVFS. It allows certain types of data processing operations to be performed directly on the storage nodes of modern parallel filesystems, near the data they manage. This is possible by exploiting the underutilized processor and memory resources of storage nodes that are implemented using general purpose servers and operating systems. In this paper, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 11 publications
1
47
0
Order By: Relevance
“…3, the input and output of a function can be both network client and disk. Similar to the previous work 13,14 , data flows in pattern 1 and pattern 3 are as same as that in the normal OSD WRITE and READ command. On this occasion, intelligent operation such as data filter (e.g.…”
Section: Flexible Data Process Patternsmentioning
confidence: 69%
See 2 more Smart Citations
“…3, the input and output of a function can be both network client and disk. Similar to the previous work 13,14 , data flows in pattern 1 and pattern 3 are as same as that in the normal OSD WRITE and READ command. On this occasion, intelligent operation such as data filter (e.g.…”
Section: Flexible Data Process Patternsmentioning
confidence: 69%
“…Since object-based storage technology may significantly influence the networked storage industry, a lot of researchers have gradually made efforts to integrate active storage into the object-based storage system. Piernas et al gave an active storage strategy implemented in userspace for Lustre parallel File System 14,10 , which proves to be faster, more flexible, portable, and readily deployable than the kernel-space version. Huston et al presented an active storage architecture called diamond 22 , used for interactive search of nonindexed data from the massive storage system.…”
Section: Related Work On Active Storagementioning
confidence: 99%
See 1 more Smart Citation
“…IOStack borrows ideas from active storage literature [13,12] as a means of building filters to enforce policies.…”
Section: Data Plane: Filter Frameworkmentioning
confidence: 99%
“…Previous work on active storage systems have shown the benefits of co-locating processing with data, such as reducing data transfer and exploiting I/O and CPU parallelism [1][2][3][4]. And more recently, the Rhea [5] system showed that filtering kernels could be extracted from Hadoop jobs using static analysis and applied transparently in cloud storage services such as Microsoft Azure [6].…”
Section: Introductionmentioning
confidence: 99%